PENGEMBANGAN MEDIA MOBILE LEARNING DENGAN APLIKASI SCHOOLOGY PADA PEMBELAJARAN GEOGRAFI MATERI HIDROSFER KELAS X SMA NEGERI 1 KARANGANYAR - Juniarti, Rani Dwi (Pendidikan Geografi, 2014)
PENGEMBANGAN MEDIA MOBILE LEARNING DENGAN APLIKASI SCHOOLOGY PADA PEMBELAJARAN GEOGRAFI MATERI HIDROSFER KELAS X SMA NEGERI 1 KARANGANYAR Rani Dwi Juniarti 1*)Sarwono2)Danang Endarto2) 1) Mahasiswa S1 Pendidikan Geografi FKIP Universitas Sebelas Maret2) Dosen Pendidikan Geografi FKIP Universitas Sebelas Maret*) E-mail : ranidwijuniarti2582@gmail.comABSTRACTThe purpose of this research are to develop mobile learning instructional media using schoology application of hydrosphere material and determine the feasibility of mobile learning instructional media using schoology applications of hydrosphere The method that applied on this research was research and development (R&D) using Analysis, Design, Development, Implementation and Evaluation (ADDIE) models modified by Molenda. Subjects of this research are media experts, material experts and 47 students as respondents. Data obtained from validation assessment of sheet material experts and media experts, and learner? assessment, interview, test and documentation. The data analysis technique used is descriptive qualitative analysis.The stages in this development of research into five steps, including: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The results of research are mobile learning instructional media using schoology applications is proferly used for geography instructional in X grade Senior High School based on media expert?s estimation through score 4 (good) on any aspect mode, ie aspects of instructional design, interface design aspects and aspects of expediency. Based on material expert?s estimation got score 4 (good) in aspects of quality material and score 5 (very good) of the advantage of material aspect. Based on one to one evaluation, small group evaluation and field trial evaluation got score 4 (good) on all properly criteria aspects. The properness of this media is also supported by an increase in the study of students seen from the average value of field trials learners during pre-test was 51.26 and the average post-test score was 79.31. From these data it can be seen that the increase occurred learners' learning outcomes with a 28.05 percentage of 54.72%.Keywords: Mobile learning, Schoology, Hydrosphere, Properness